Incorporating Pavement Smoothness Benefits to Enhance the Iowa Department of Transportation's Pavement Type Determination Process. Issue 5 (May 2020) - Grogg, Max; Smith, Kelly; Williges, Chris; Schram, Scott
The Federal Highway Administration (FHWA)'s Pavement Policy as codified in 23 CFR 626 states, "Pavement shall be designed to accommodate current and predicted traffic needs in a safe, durable, and cost effective manner" to be eligible for federal highway funding. To meet this requirement, state highway agencies have developed pavement type determination (PTD) policies, also known as pavement type selection, and implemented pavement management. Iowa Department of Transportation (DOT)'s PTD has been in place for many years; but in 2018, Iowa DOT looked at enhancing their PTD process to address gaps between past practice and best practice. Among the enhancements, user benefit as defined by pavement smoothness was utilized when net present value (NPV) alone could not definitively distinguish a preferred alternative. The smoothness benefit would become the divisor in a cost–benefit (C/B) ratio that would be used to determine the preferred alternate for the PTD. The cost portion of the ratio would remain the NPV of agency costs for the construction and projected rehabilitations during the analysis period. After a literature review and interviews of comparable state DOTs, several modifications to Iowa DOT's PTD and the C/B ratio were analyzed and adopted. The modifications range from accepted practice changes, such as the use of a longer analysis period (50 years), to unconventional techniques, such as the consideration of smoothness. Iowa DOT believes these changes provide a more robust PTD. They are also considering additional improvements based upon additional research and policy making.